Heart failure in subjects with chronic kidney disease: Best management practices - Aslam, Farhan (Baishideng Publishing Group Co., Limited, 2010)
Renal dysfunction is common in patients with heart failure (HF) and can complicate HF therapy. Treating patients with HF and kidney disease is difficult and requires careful assessment, monitoring and balancing of risk between potential benefits of treatment and adverse impact on renal function. In this review, we address the pathophysiological contexts and management options in this adversarial relation between the heart and the kidney, which exists in a substantial proportion of HF patients. Angiotensin converting enzyme inhibitors and β-blockers are associated with similar reductions in mortality in patients with and without renal insufficiency but usually are less often prescribed in patients with renal insufficiency. Careful monitoring of side effects and renal function should be done in all patients with renal insufficiency and prompt measures should be adopted to prevent further complications.